Hadits Teologi (Kajian Tentang Dosa Besar dalam Kitab Shahih Al-Bukhari Bab Al-Adab No. 5520) - Retno sirnopati (TAFAQQUH: Jurnal Hukum Ekonomi Syariah Dan Ahwal Syahsiyah, 2016)
The Qur'an is the revelation that God revealed to humanity through Muhammad as His messenger, while the hadith of Muhammad himself comes in the form of words, actions, judgments or hammiyah (desire / aspiration) Muhammad himself an apostle for the people humans to the universe (Rahmatan lil 'alamin). The following study is the hadith about the great sin of shirk and include disobedience to parents along with an explanation bagimana relevance to other woods hadith which speaks about the great sin through different sanad. There was also a description in this paper will mengakaji hadith about Shirk by looking at the Koran that talk also about Shirk, then seek to see a contextual interpretation than the Qur'an and al-hadith talking about the great sin.